Industrial hygiene: tutorial - Кавешников, В. С. кардиология 19750627 Владимир Сергеевич (Siberian State Medical University, 2021)
The tutorial on Hygiene is prepared in accordance with the Federal State Educational Standard of Higher Professional Education, for medical students. The textbook includes the main topics for practical classes on "Industrial hygiene" and reviews hygienic significance, pathogenic effects, methods and equipment for measurements, regulation and prevention of professional pathology regarding such industrial factors as - dust, harmful chemicals, noise, infrasound, ultrasound, vibration, ionizing radiation. The textbook also reviews the concepts of severity and intensity of work, methods for their assessment, pathogenic role and principles of regulation of harmful working conditions, the concept of fatigue and its prevention. In presenting the material, the current regulatory documents - State Stand ards, SNiPs and SanPiNs were used.